Mulberry leaves protect rat tissues from immobilization stress-induced inflammation - Lee, C.Y.; Cheng, H.M.; Sim, S.M. (2007)
The ability of the antioxidants in the mulberry leaves to protect Sprague-Dawley rats from injuries caused by immobilization stress was studied as an indicator of the tissue bioavailability of antioxidants. Nitrite level, lipid peroxidation and total antioxidant activity (TAA) in the plasma and tissues were measured. There were hypertrophy of the adrenal glands and kidneys, significant increased levels of nitrite in the plasma and adrenal glands, elevated thiobarbituric acid reactive substances TBARS) in the plasma, kidneys and spleen, and a reduction of TAA in the plasma, liver, adrenal glands, kidneys and spleen of the immobilized rats. Antioxidants in the mulberry leaf extract suppressed the increase of nitrite and TBARS. Adrenal glands appeared to be the target organ of the antioxidants in the leaf extract. The low dose mulberry antioxidants were more effective than pure rutin (4 mg/day) to protect the cells against inflammation and peroxidation induced by stress.